The Use of Antiseptic Solutions in the Prevention and Management of Penile Prosthesis Infections: A Review of the Cytotoxic and Microbiological Effects of Common Irrigation Solutions. Issue 6 (1st June 2019) - Pan, Shu; Rodriguez, Dayron; Thirumavalavan, Nannan; Gross, Martin S.; Eid, J. Francois; Mulcahy, John; Munarriz, Ricardo
ABSTRACT: Introduction: The Mulcahy salvage fundamentally altered the management of penile prosthesis infections (PPI). Central to this procedure is a sequence of antiseptic irrigations that aims to remove and eradicate pathogenic microflora from the infected field, thus preparing for immediate reimplantation. The antiseptic solutions and their respective concentrations, however, have never been evaluated for efficacy. Aim: This review critically examines 3 commonly used antiseptic irrigation solutions (povidone-iodine [PVI], hydrogen peroxide [H2 O2 ], and chlorhexidine gluconate [CHG]) in terms of their antimicrobial activity, cytotoxicity, and clinical use. Methods: A PubMed literature review was performed on articles published between 2003 and 2018. Both preclinical as well as clinical studies from various surgical disciplines were included in this review. Main Outcome Measure: The original salvage protocol selected for irrigation solutions at concentrations that are likely detrimental to native tissue. Results: All 3 agents demonstrate in vitro cytotoxic effects at subclinical concentrations, but H2 O2 is associated with the most significant deleterious properties. It does not seem to broaden antimicrobial coverage beyond what is covered by PVI. Dilute PVI (0.35–3.5% with exposure time of at least 3 minutes) possesses the most robust clinical evidence as an intraoperative adjunct, reducing the incidence of postoperative infectious complications. chlorhexidine gluconate is a promising new agent but lacks clinical data. Clinical implication: Improvements in the salvage protocol are warranted based on current evidence. Careful selection of lavage solution and usage of the lowest necessary concentration will help achieve desired antimicrobial activity while avoiding native tissue cytotoxicity. Strength and limitation: The study is limited by its retrospective nature, and the heterogeneity of literature reviewed precluded a formal meta-analysis. Furthermore, future studies will need to address the roles of normal saline and antibiotic irrigations as intraoperative adjuncts for infection prevention. Conclusion: Diluted PVI (0.35–3.5% for 3 minutes) may be beneficial in the prevention of PPI. Evidence supports its use both in the setting of primary implantation as well as salvage of infected hardware. An improved, evidence-based protocol may increase positive outcomes of urologic prosthetic surgery.